2016
DOI: 10.1186/s40635-016-0083-4
|View full text |Cite
|
Sign up to set email alerts
|

Critical illness polyneuropathy in ICU patients is related to reduced motor nerve excitability caused by reduced sodium permeability

Abstract: BackgroundReduced motor and sensory nerve amplitudes in critical illness polyneuropathy (CIP) are characteristic features described in electrophysiological studies and due to dysfunction of voltage-gated sodium channels. Yet, faulty membrane depolarization as reported in various tissues of critically ill patients may cause reduced membrane excitability as well. The aim of this study was to compare the pathophysiological differences in motor nerve membrane polarization and voltage-gated sodium channel function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 28 publications
0
21
1
2
Order By: Relevance
“… 8 , 9 Preliminary findings have suggested that, rather than degeneration of axons, the reduction in the excitability of motor and sensory fibers is due to a hyperpolarized shift in the voltage dependence of sodium caused by inactivation of sodium channels in peripheral nerves during the acute phase of critical illness. 10 …”
Section: Introductionmentioning
confidence: 99%
“… 8 , 9 Preliminary findings have suggested that, rather than degeneration of axons, the reduction in the excitability of motor and sensory fibers is due to a hyperpolarized shift in the voltage dependence of sodium caused by inactivation of sodium channels in peripheral nerves during the acute phase of critical illness. 10 …”
Section: Introductionmentioning
confidence: 99%
“…Another theory is that the chronic inflammation in CIP patients increases vascular permeability and leads to vasogenic edema [27]. Fenzi et al biopsied the superficial peroneal nerve of critically ill patients with CIP and found decreased myelin density and axonal degeneration.…”
Section: Proposed Mechanismsmentioning
confidence: 99%
“…On the other hand, the explanation of the reduced motor and sensory nerve amplitudes in CIP is reported to be due to dysfunction of voltage-gated sodium channels, as abnormal membrane depolarization found in different tissues of critically ill patients may cause reduced membrane excitability [35]. Also, Z'Graggen et al [36] described membrane depolarization of motor nerves in patients with CIP.…”
Section: Critical Illness Polyneuropathy and Myopathy And Neurophysiomentioning
confidence: 99%